FIRE SAFETY DESIGN OF A 5 STOREY OFFICE BUILDING: FIRE SUPPRESSION (FUDMA JOURNAL OF SCIENCES, 2024)
A design of fire suppression system for Asha Office Building was conducted.   It is a proposed 5 storey administrative building with a width, length and height of 65m, 47m and 17m respectively as well as a ceiling heights of 3m throughout except ground floor which is 4m. A fire risk assessment of the building was conducted and the outcome revealed a restaurant as the most hazardous component of the building and hence a worst case scenario. A detailed design of a wet sprinkler system installation and operation in the restaurant showed that 15 sprinkler heads are required in 5 range pipes. The spacing between sprinkler heads (S) and sprinkler range pipes (D) are 3.67m and 3.0m respectively. However, only 6 sprinklers will be required to operate in a fire. A total water flow rate and the total pressure required for the operation of the six sprinklers are 444.49 lit/min and 1.7723 bar. Equally, a suction pump pressure of 7.7 bar is required to provide the necessary water volume and pressure to the sprinkler system. A CFAST simulation for a restaurant that is sprinklered revealed a peak temperature of about 400oC at 350 seconds and began to drop as a result of the effect of sprinklers. But, for an unsprinklered restaurant, a peak temperature of about 900oC at 700 seconds was attained. Therefore, it can be deduced that flashover will not occur in a sprinklered restaurant since it is less than the recommended temperature for...
Keywords: Fire; Safety; Suppression